Educational Environments and Children's Physical Activity and Sedentary Behaviors - (:unkn) unknown (My University, 2023)
Children and adolescents spend the majority of their day engaged in sedentary behaviors (SB), while also not meeting physical activity (PA) recommendations. The failure to develop and maintain health enhancing behaviors from a young age may impact an individual throughout their life. With children and adolescents spending a large proportion of their waking hours in a school setting, the educational environment presents an opportunity in which children and adolescents’ PA and SB can be positively influenced. Therefore, the purpose of this dissertation was to explore how children and adolescent’s school time PA and SB are associated with the educational setting, and how these behaviors change over the course of the school year and in response to non-traditional classroom settings. To address this purpose, three individual studies were completed. Study 1: Comparison of measures of elementary student’s classroom postural behaviors using direct observation and accelerometry in a school setting. The results of our research are only as good as the measures used, therefore to begin this series of studies two commonly used objective methods to assess children’s PA and SB were compared. Specifically, the inclinometer function of a hip-worn Actigraph GT3X+ accelerometer (ACC) and direct-observation (DO) were evaluated in their measurement of child and adolescent posture within a classroom environment that included stand-biased and traditional seated desks. Our results suggest that the measurement of both sitting and standing while in either a stand-biased or traditional seated desk were significantly different between DO and ACC, with DO consistently recording a higher proportion of time spent sitting, and a lower proportion of time standing regardless of desk assignment. The difference between DO and ACC measures of sitting (-18.9%; p=0.041) were significantly smaller when students used a stand-biased compared to a traditional seated desk. There was no significant difference between DO and ACC measures of standing between desk types, and lower limb fidgeting was found to have no main or interaction effect between desk type and differences of postural measures. It is important to remain cognizant of the methodologies used to assess youth behaviors, and the influence these measurement techniques can have on intervention outcomes involving environmental and other behavioral modifications. Study 2: An exploration into the variation of children’s in-school physical activity across the school year. Study two explored the variation in children and adolescents PA behaviors during active periods of the school day across the school year. Participating students completed a survey on five separate occasions throughout the school year, assessing activity levels during active transportation to and from school, at recess, and in physical education class. Our results suggest that overall, the weekly minutes that children and adolescents spent engaging in moderate- to vigorous-intensity PA (MVPA) remained relatively stable during recess (Avg: 42.2±12.2 minutes/week) and physical education class (Avg: 17.7±5.6 minutes/week) throughout the year. Statistically significant differences were found in the estimated weekly minutes of MVPA accumulated during active transportation to- and from-school, with the greatest accumulation occurring in September (To-School: 15.3±5.7 minutes/week; From-School: 32.0±10.5 minutes/week), and the lowest accumulation of MVPA to-school and from-school occurring in December (13.9±6.5 minutes/week; p=0.01) and March (28.5±11.9 minutes/week; p
Keywords: Adolescent; Classroom; Elementary; Youth